2019
DOI: 10.1002/cam4.2609
|View full text |Cite
|
Sign up to set email alerts
|

Palliative resection or radiation of primary tumor prolonged survival for metastatic esophageal cancer

Abstract: PurposeWe aimed to explore the value of palliative resection or radiation of primary tumor for metastatic esophageal cancer (EC) patients.MethodsSurveillance, Epidemiology, and End Results database was used for identifying metastatic EC patients. The patients were divided into resection and nonresection groups. And patients without resection were divided into radiation and nonradiation groups. Propensity score matching (PSM) analyses were adopted to reduce the baseline differences between the groups. Cancer sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…In a large cohort of 12,683 patients with metastatic EC, Guttmann et al ( 13 ) reported that definitive-dose (≥50.4 Gy) CRT was associated with superior survival compared to CT alone (median OS 8.3 vs. 11.3 months). As shown in Table 2 , the clinical survival outcomes of the metastatic population in this study were highly consistent with those of previous studies ( 13 , 18 21 ).…”
Section: Discussionsupporting
confidence: 90%
“…In a large cohort of 12,683 patients with metastatic EC, Guttmann et al ( 13 ) reported that definitive-dose (≥50.4 Gy) CRT was associated with superior survival compared to CT alone (median OS 8.3 vs. 11.3 months). As shown in Table 2 , the clinical survival outcomes of the metastatic population in this study were highly consistent with those of previous studies ( 13 , 18 21 ).…”
Section: Discussionsupporting
confidence: 90%
“…However, none of them combined surgery with radiotherapy to provide new ideas to treat patients with MEC. A study by Xu et al [ 19 ] reported that radiotherapy and palliative resection of the primary tumor could prolong the survival of patients with MEC. However, they have not conducted a definitive study on the appropriate sequence of radiotherapy and surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no consensus on whether palliative radiotherapy or surgery is of value in metastatic EC. Several studies have suggested that palliative radiotherapy and surgery can improve survival in patients with metastatic EC [9,11,24] . Moreover, several retrospective studies have found that primary tumor resection may be considered a strategy for selected patients with stage IV EC who achieve a favorable response to systemic chemotherapy [17,25] .…”
Section: Discussionmentioning
confidence: 99%